2019
DOI: 10.1111/bju.14874
|View full text |Cite
|
Sign up to set email alerts
|

Characterising ‘bounce‐back’ readmissions after radical cystectomy

Abstract: ObjectiveTo examine predictors of early readmissions after radical cystectomy (RC). Factors associated with preventable readmissions may be most evident in readmissions that occur within 3 days of discharge, commonly termed 'bounce-back' readmissions, and identifying such factors may inform efforts to reduce surgical readmissions. Patients and MethodsWe utilised the Healthcare Cost and Utilization Project's State Inpatient Databases to examine 1867 patients undergoing RC in 2009 and 2010, and identified all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Hospital readmission was required in seven patients (11.7%; 2 from the LRC and 5 from the ORC groups, respectively, P =0.42). This was in line with other studies which reported a relatively high readmission rate of 8.6–28% after radical cystectomy [ 25 , 26 ]. In a large cohort of 8827 Medicare patients, there was no difference in rates of hospital readmissions between minimally invasive and open radical cystectomy, which suggests that the high readmission rates are inherent to radical cystectomy itself regardless of the approach [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Hospital readmission was required in seven patients (11.7%; 2 from the LRC and 5 from the ORC groups, respectively, P =0.42). This was in line with other studies which reported a relatively high readmission rate of 8.6–28% after radical cystectomy [ 25 , 26 ]. In a large cohort of 8827 Medicare patients, there was no difference in rates of hospital readmissions between minimally invasive and open radical cystectomy, which suggests that the high readmission rates are inherent to radical cystectomy itself regardless of the approach [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…All readmissions within 90 days of an operation were analyzed for primary indication, complications, and interventions. Readmissions within 3 days of discharge were classified as early readmissions consistent with readmission literature 22 . The primary reason for readmission was classified, in order of priority, as technical (pancreatic or nonpancreatic anastomotic leak), infectious (surgical site or other infections not resulting from a technical complication), or medical/metabolic (DGE, failure to thrive, poor oral intake, or another medical problem not resulting from a technical or infectious cause).…”
Section: Methodsmentioning
confidence: 99%
“…Reasons for readmission can include failure to thrive, wound or pelvic infection, venous thromboembolism, or small-bowel obstruction. 3,4 Readmission not only is associated with increased risks for the patient from a clinical standpoint, but also can have a significant cost burden on the health care system. 5,6 Several studies have identified clinical or patient risk factors associated with readmission after RC.…”
mentioning
confidence: 99%